2020
DOI: 10.1158/1538-7445.am2020-5750
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5750: The antidepressant vortioxetine reverses cognitive deficits associated with androgen deprivation therapy for the treatment of prostate cancer in healthy rats

Abstract: First-line treatment for prostate cancer includes androgen deprivation therapy (ADT). However, this intervention can induce severe cognitive impairments in more than half of patients and increases the likelihood of dementia or Alzheimer's disease. Long-term occurrence of these impairments can significantly reduce quality of life for cancer survivors and ultimately impacts their families and caregivers. Thus, it is important to improve the cognitive side effects of ADT, as 45% of prostate cancer patients will u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Cognition is dependent on functional plasticity, including in the circuitry between the mPFC and hippocampus. In our previous study, we found that vortioxetine reversed the attenuated responsivity induced in mPFC- and hippocampus-related circuitry after surgical castration in young rats [15]. The fact that vortioxetine was also effective in reversing ADT-induced changes in evoked local field potentials of middle-aged rats is important to informing the potential utility of vortioxetine to improve cognition impaired by ADT in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cognition is dependent on functional plasticity, including in the circuitry between the mPFC and hippocampus. In our previous study, we found that vortioxetine reversed the attenuated responsivity induced in mPFC- and hippocampus-related circuitry after surgical castration in young rats [15]. The fact that vortioxetine was also effective in reversing ADT-induced changes in evoked local field potentials of middle-aged rats is important to informing the potential utility of vortioxetine to improve cognition impaired by ADT in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we reported results using young adult male Sprague-Dawley rats [14, 15]. Surgical castration was used to isolate the cognitive effects of testosterone depletion from potentially confounding pharmacological effects of drugs used for chemical castration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations